The Effectiveness Of Rosetta Stone On Vocabulary Mastery Through Seventh Grade At Smp Islam Al Azhaar Tulungagung In Academic Year 2023/2024 - Nurhidayah Nurhidayah; Ika Rakhmawati (Institut Nalanda, 2024)
English language proficiency has an important role in communication, daily life, and academic pursuits. English language proficiency opens up future opportunities such as employment and higher education, which often require proficiency standards such as TOEFL or IELTS. Even though it is a compulsory subject in school, many have difficulty learning English. The four main skills to be developed are reading, writing, listening, and speaking, all of which are essential for communicative competence and vocabulary mastery. In response to these challenges, educators are increasingly using technology such as the Rosetta Stone app. This app is known for its Dynamic Immersion and TruAccent features that make learning interactive and effective. This study aims to determine the effectiveness of the use of the Rosetta Stone application on the vocabulary mastery of grade VII students at Al Azhar Islamic Junior High School Tulungagung. The experimental research method was used by dividing the research subjects into two groups, namely the experimental group that used the Rosetta Stone application and the control group that did not use it. The results showed that students' vocabulary scores increased significantly from 73.20 to 90.80 after using this application. Statistical analysis with paired sample t-test confirmed the effectiveness of the application in improving students' vocabulary mastery and interest in learning English. The study confirms the positive impact of technological interventions such as Rosetta Stone in improving English language skills, validating their efficacy through rigorous statistical analysis and practical results.